Bhayangkara and Platypus: The Cooperation between Indonesian National Police (Polri) and Australian Federal Police (AFP) in Dealing With Terrorism Threat in the Post of Lombok Treaty - Heni Yekti Pamulatsih; Anak Agung Banyu Perwita (Universitas Diponegoro, 2020)
Terrorism has become the utmost concern of many countries in the world including Indonesia and Australia. Indonesia and Australia have signed a security agreement on 13 November 2006, which was known as Lombok Treaty to promote security relations between the two countries. This article aimed to discuss the security cooperation between Indonesia and Australia especially between Indonesian National Police and Australian Federal Police cooperation in addressing terrorism threat in Indonesia. By using descriptive qualitative method, this article scrutinizes the implementation of security cooperation especially cooperation between Indonesian National Police (POLRI) and Australian Federal Police (AFP) during 2012-2017. It was found that the type and the nature of cooperation between the two police institution could be divided into several dimension. It covered to further build cybercrime investigation satellite office (CCISO), increase personnel capacity building, and promote intelligence exchange to address terrorism threat.